Low antispike antibody levels correlate with poor outcomes in COVID‐19 breakthrough hospitalizations. (24th March 2022) - Sanghavi, Devang K.; Bhakta, Shivang; Wadei, Hani M.; Bosch, Wendelyn; Cowart, Jennifer B.; Carter, Rickey E.; Shah, Sadia Z.; Pollock, Benjamin D.; Neville, Matthew R.; Oman, Sven P.; Speicher, Leigh; Siegel, Jason; et al.
Abstract: Background: While COVID‐19 immunization programs attempted to reach targeted rates, cases rose significantly since the emergence of the delta variant. This retrospective cohort study describes the correlation between antispike antibodies and outcomes of hospitalized, breakthrough cases during the delta variant surge. Methods: All patients with positive SARS‐CoV‐2 polymerase chain reaction hospitalized at Mayo Clinic Florida from 19 June 2021 to 11 November 2021 were considered for analysis. Cases were analyzed by vaccination status. Breakthrough cases were then analyzed by low and high antibody titers against SARS‐CoV‐2 spike protein, with a cut‐off value of ≥132 U/ml. Outcomes included hospital length of stay (LOS), need for intensive care unit (ICU), mechanical ventilation, and mortality. We used 1:1 nearest neighbor propensity score matching without replacement to assess for confounders. Results: Among 627 hospitalized patients with COVID‐19, vaccine breakthrough cases were older with more comorbidities compared to unvaccinated. After propensity score matching, the unvaccinated patients had higher mortality (27 [28.4%] vs. 12 [12.6%], p = 0.002) and LOS (7 [1.0–57.0] vs. 5 [1.0–31.0] days, p = 0.011). In breakthrough cases, low‐titer patients were more likely to be solid organ transplant recipients (16 [34.0%] vs. 9 [12.3%], p = 0.006), with higher need for ICU care (24 [51.1%] vs. 22 [11.0%], p = 0.034), longer hospital LOS (median 6 vs. 5 days, p = 0.013), and higher mortality (10 [21.3%] vs. 5 [6.8%], p = 0.025) than high‐titer patients. Conclusions: Hospitalized breakthrough cases were more likely to have underlying risk factors than unvaccinated patients. Low‐spike antibody titers may serve as an indicator for poor prognosis in breakthrough cases admitted to the hospital. Abstract :